AB0573 ASSESSMENT OF PRESENCE, SEVERITY AND RISK FACTORS OF POST- THROMBOTIC SYNDROME IN VASCULAR BEHÇET DISEASE: MUTICENTERED RETROSPECTIVE STUDY. (June 2019) - Aksoy, Aysun; Colak, Seda; Omma, Ahmet; Yağız, Burcu; Seniz, Belkis Nihan; Bolca, Naile; Ergelen, Rabia; Direskeneli, Haner; Alibaz-Oner, Fatma
Abstract : Background: DVT(deep venous thrombosis) is the most common form of vascular Behçet Disease(VBD).Post-trombotic syndrome(PTS) developing after a thrombotic event in lower extremity is the most important complication of DVT and affects negatively patients' quality of life. Objectives: We aimed to assess presence, severity and risk factors of PtS and venous disease spesific quality of life in VBD Methods: This study included 96 BD patients (Female/Male:18/78, mean age: 38.8±8.74)with DVT from 3 tertiary Rheumatology centers in Turkey.When vascular involvement developed, mean age was 32.7±8.65(female: 35.4±10.7; male: 32.09±8; p>.005) Villalta scale is used to assess PTS and according to scale; PTS is present if score >4 and degree of PTS mild, moderate and severe if score 5-9, 10-14, >14 respectively. The Venous Disability Score(VDS) and the Venous Clinical Severity Score(VCSS) were used for the assessment of venous disease. Venous disease-specific QoL was measured through Venous Insufficiency Epidemiological and Economic Study Quality of Life/Symptom (VEINES-QoL/Sym) questionnaire.All patients were reanalyzed using color Doppler USG in the Radiology Department, by a radiologist.In each patient, a total of 16 superficial and deep veins in both legs were assessed for the presence or absence of obstruction, recanalization, reflux, and collaterals within 1 weeks following the clinical examination. Results: During venous assessment, median disease duration was 9(0-34)years. Eighty(84.2%) patients were under ımmunsupressive(IS) treatment and 13 of these patients were under anticoagulation treatment in addition to ISs. Duration between first vascular event and venous assessment was 6(1-26)years. PTS was present in 57(61.3%) out of 93 patients and severe PTS was present in 19(19.8%)patients.There was no association between the presence of PTS and sex, disease diagnosis age, age during DVT, presence of relaps. There was no difference between patients with or without PTS according to the anticoagulant usage (p=0.817).Doppler ultrasound examination showed bilateral at 31(31.4%) patients and both upper and lower involvment at 40(47.6%) patients.But there is no statically significant relationship between presence of PTS and Doppler findings. In addition to these, there is no statically significant association between PTS and presence of reflux-trombosis at any vessel in the affected leg, but there is a correlation between severe PTS and reflux(r=0.224, p:0.096).VCSS have positive correlation with the presence of reflux(p:0.041, r:0.224). VEINES-QoL/Sym, VCSS and BSAS were significantly worse in patients with PTS.(Table1 ) Conclusion: In this study, we found that PTS in lower extremity develops in more than half of the patients with VBD during follow-up, and didn't found any predictor factor for develeopment of PTS. About one third of patient with PTS had severe PTS. PTS is an important clinical problem for physicians treating VBD in daily practice.It should be taken into account as much as preventing vascular relapses during follow-up of patients with VBD. Disclosure of Interests: None declared